Effect of causal attribution on acculturative subjective well-being : mainland Chinese students in Singapore. - Lo, Chrystella Hui Min. (2010)
The present study puts together acculturation and subjective well-being, studying it as a single construct, termed acculturative subjective well-being. 100 Mainland Chinese students were measured for their level of subjective well-being and stress both in Singapore as well as when they were in China, in order to measure their acculturative subjective well-being and acculturative stress. Results showed that their level of acculturative subjective well-being were highly correlated with their level of subjective well-being in their homeland. Results also showed marginal significance of causal attribution on subjective well-being, with the highest, significant others, having negative correlation, and internal attribution being the only style with positive correlation.